Review: Detection and Classification of Plants Leaf Diseases - Shahir, Twinkle; Raut, Monali; Khode, Shraddha; Bhagat, Runali; Charde, Vaishnavi (IJRDO -Journal of Computer Science Engineering, 2015)
The aim of this project is to design, implement and evaluate an image processing software based solution for automatic detection and classification of plant leaf disease. We present fast, automatic, cheap and accurate image processing based solution. This solution is composed of four main phases. First the digital images are acquired from the field or environment using digital camera. Image preprocessing technique noise is removed by filtering technique. Next, in the second phase, the images are segmented using the K-means clustering technique. In the third phase, we calculate the texture features for the segmented infected objects. Finally, in the fourth phase the extracted features are passed through a pre-trained neural network